A peculiar new beetle from Brazil associated with a cave habitat (Coleoptera, Carabidae, Clivinini) - Balkenohl, Michael; Pellegrini, Thais Giovannini; Zampaulo, Robson De Almeida (Zootaxa, 2018)
The new species Ardistomis ferreirai sp. nov. is described and illustrated. Some specific characters are discussed together with a possible correlation to the species subterranean way of life. Available ecological data and recordings are provided by description of the caves and the specific threats to the caves are indicated.